Plume origin of the Central Arctic uplifts evolution in the Amerasian Basin of the Arctic Ocean - Verba V.V.; Truhalev A.I. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2016)
Geological and geophysical aspects of the Central Arctic Elevations in the Arctic Ocean have been analyzed in order to consider their correspondence to signs of a mantle plumes activity accepted by most scientists. The manifestation in topography (vast arched uplift), extensive Late Mesozoic intraplate basaltic magmatic activity (High Arctic Large Igneous Province, HALIP), and gravimetric and magnetometric characteristics have been outlined to indicate that the area of the Central Arctic Elevations is a block of the ancient continental crust. The block underwent intensive destructive transformations driven by mantle upwelling but with preservation of general geophysical properties of continental crust, and subsidence up to bathyal depths at the neotectonic level.
Keywords: ARCTIC; AEROMAGNETICS; MANTLE PLUME; HIGH ARCTIC LARGE IGNEOUS PROVINCE